Youths and agribusiness development in Kenya - Abwao, Martin (Studia Mundi – Economica, 2014)
In many parts of the world, agriculture has been left for the old people and illiterate men and women in the rural areas. Unfortunately, these people view agribusiness with a lot of suspicion. For them, agribusiness is synonymous with big business/ capital, transnational corporations, globalization, international capital, export crops and large-scale plantations. More often than not, these are seen to culminate into exploitation of local people and resources. Adoption of new technology, inputs and engagement with new markets are critical for the enhancement of agricultural productivity in Kenya. With the new free primary and secondary education in Kenya, a higher population of youths are literate hence able to adopt new technology and engage with the new markets in the agricultural industry. Since agribusiness is all about innovation in line with value addition, youths are privileged to have technological, mental and physical capacity to think and execute accordingly. When projecting into the future of agribusiness in Kenya, the youths are inevitably vital. It is also undoubted fact that the critical role played by agribusiness in agri-food sector requires high level of flexibility and dynamism among the people involved. This vibrant agriculture will lead to fairly adequate availability of employment opportunities within the sector. Specifically, jobs will move from informal to formal, small scale organizations to formal and large scale; from artisan to more industrial processing; from wet market to store based retail and small market centers will grow to towns and cities. The main objective of this research is to find out the diverse potentials among the youths that are essential for agribusiness development in Kenya. It will focus on knowledge or literacy levels among the youths; ability to think or innovate, training potentials and health conditions among others. It will also look into the physical resources available at their disposal e.g land size, shelter, livestock, capital etc. We will also go an extra mile to find various challenges that discourages youths from engaging in agribusiness ventures. The results of these findings will enable us to conclude whether the youths are indeed essential for the agribusiness development in Kenya or not.